2018
DOI: 10.1007/s10295-018-2078-5
|View full text |Cite
|
Sign up to set email alerts
|

Production of optically pure l(+)-lactic acid from waste plywood chips using an isolated thermotolerant Enterococcus faecalis SI at a pilot scale

Abstract: Utilization of renewable and low-cost lignocellulosic wastes has received major focus in industrial lactic acid production. The use of high solid loadings in biomass pretreatment potentially offers advantages over low solid loadings including higher lactic acid concentration with decreased production and capital costs. In this study, an isolated Enterococcus faecalis SI with optimal temperature 42 °C was used to produce optically pure L-lactic acid (> 99%) from enzyme-saccharified hydrolysates of acid-impregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…In contrast, the OTU number increased during anaerobic fermentation, which may be associated with inoculation with E. faecium and the growth of some other LA bacteria. The main phyla (Cyanobacteria, Proteobacteria, and Firmicutes) found in the present study were also obtained in some other studies related to SSF (29,30).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In contrast, the OTU number increased during anaerobic fermentation, which may be associated with inoculation with E. faecium and the growth of some other LA bacteria. The main phyla (Cyanobacteria, Proteobacteria, and Firmicutes) found in the present study were also obtained in some other studies related to SSF (29,30).…”
Section: Discussionsupporting
confidence: 88%
“…Members of the heat-tolerant genus Bacillus are effective at degrading proteins and cellulose during SSF due to their strong hydrolytic abilities (29). Enterococcus is a mesophilic genus whose members generate LA (30). Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, at 5.2-m 3 scale, only 91.5 g·L −1 of LA was obtained, with a productivity of 0.88 g·L −1 ·h −1 . Additionally, a longer lag phase was observed due to the differences in the oxygen levels of both bioreactors tested [37]. Wee et al [38] conducted a 200-L pilot-scale batch using corn steep liquor as a nitrogen source and glucose as a the carbon substrate.…”
Section: Lactic Acidmentioning
confidence: 99%
“…Process scale-up is an important aspect for industrial biofuel or biochemical production [32,33]. Based on the optimal condition achieved at the test tube scale (16.6 mg/L at 72-h timepoint using a 1:1 inoculation ratio with 33.5 °C temperature), we sought to evaluate the scalability of this synthetic co-culture at a shake flask scale with an extended fermentation period (96 h).…”
Section: Scale Up Resveratrol Production Using the Synthetic Consortimentioning
confidence: 99%
“…Previous studies have shown that utilizing high cell density microbial bioprocesses can increase volumetric productivity and alleviate the impact of toxic growth inhibitors [32,38,39]. Similarly, increasing co-culture inoculum size of S. cerevisiae and E. coli led to an improvement in naringenin production [31].…”
Section: Increased Net Inoculum Size Of the Co-culture Improves Resvementioning
confidence: 99%